Molecular surveillance of chloroquine drug resistance markers (Pfcrt and Pfmdr1) among imported Plasmodium falciparum malaria in Qatar. (17th February 2018) - Acharya, Anushree; Bansal, Devendra; Bharti, Praveen K.; Khan, Fahmi Y.; Abusalah, Salem; Elmalik, Ashraf; ElKhalifa, Mohammed; Mohapatra, Pradyumna K.; Mahanta, Jagadish; Sehgal, Rakesh; Singh, Neeru; Sultan, Ali A.
Abstract: Imported malaria has been a great challenge for public health in Qatar due to influx of large number of migrant workers. Antimalarial drug resistance has emerged as one of the greatest challenges facing malaria control today. Monitoring parasite haplotypes that predict susceptibility to major antimalarial can guide treatment policies. This study aimed to determine molecular drug resistance pattern in imported malaria cases in Qatar. Blood samples from the uncomplicated P. falciparum malaria patients were collected at Hamad General Hospital, HMC, Doha, Qatar. The samples were further confirmed by nested-polymerase chain reaction (PCR) for P. falciparum . Molecular markers of chloroquine ( Pfcrt and Pfmdr1 ) were analyzed by using nested PCR- RFLP method to determine the key point mutations associated with chloroquine (CQ) drug resistance. A total 118 blood samples were positive for P. falciparum . Overall, by RFLP, 72% harboured wild type allele (N86) of Pfmdr1 gene. The prevalence of Pfcrt mutant (T76), WT (K76) and mixed alleles (K76T) was 63.6% ( n  = 75), 22.9% ( n  = 27) and 13.5% ( n  = 16), respectively. Mean parasitaemia level was higher among the wild type alleles of Pfcrt gene as compared to the mixed/mutant alleles whereas mixed alleles of Pfmdr1 gene having high parasitaemia. Molecular surveillance strategy based on imported malaria cases can be used to detect and track CQ drug-resistant malaria. The data presented here might be helpful for enrichment of molecular surveillance of antimalarial resistance and will be useful for developing and updating antimalarial guidance for non-immune imported cases in Qatar.